Setting a sustainable trajectory : a pedagogical theory for Christian worldview formation - Lindemann, Rob (Wipf & Stock, 2018)
Many Christian colleges promote worldview formation as part of their purpose and learning objectives. An institution teaches a worldview with intentionality, enculturates it through community life, reinforces it through human interaction, and passes it on through symbols and stories. Accreditation standards often require colleges to demonstrate how their programs support the development of a biblical worldview. This requirement necessitates a search for teaching and assessment approaches that can best serve this essential goal. In this book, the author reports on qualitative research with Bible colleges and offers a pedagogical theory for supporting students' lifelong development of worldview. This theory shows how college teachers can clarify their goals, set relevant objectives, employ effective teaching strategies, and design helpful assessment methods. --